Evaluating peripheral blood lymphocyte subset composition and lipopolysaccharide-induced cytokine secretory activity in mononuclear leukocyte cultures from patients with febrile and meningeal forms of tick-borne encephalitis - Ekaterina N. Ilyinskikh; O. V. Voronkova; A. V. Reshetova; R. R. Hasanova; I. E. Esimova; N. A. Chernyshov; O. V. Yampolskaya; A. V. Yampolskaya; E. M. Polomoshnova; E. V. Minakova (Инфекция и иммунитет)
Introduction.Multiple studies on immune response in patients with various clinical forms of tick-borne encephalitis (TBE) have shown conflicting results. The study aim was to estimate the changes in peripheral blood lymphocyte subset counts and activity of spontaneous and lipopolysaccharide (LPS)-stimulated cytokine production in the mononuclear leukocyte cultures in patients with febrile and meningeal acute TBE.Materials and methods.Groups 1 and 2 included 16 and 12 patients with febrile and meningeal acute TBE, respectively. The control group included 13 healthy donors. Hemogram and T-lymphocyte, T-helper cell, T-cytotoxic and NK cell counts were analyzed by flow cytometry at week 1 of the disease as well as the spontaneous and LPS-stimulated secretion levels of TNFα, IL-1β, IL-6, IL-10, IL-8, and MCP-1 were assessed by ELISA in the supernatants of mononuclear cell cultures twice: during hospitalization and two weeks later. Statistical analysis was performed by the Mann–Whitney U-test, and Wilcoxon test.Results.Group 2 demonstrated significant decrease in spontaneous and/or LPS-stimulated levels of proinflammatory cytokines IL-1β, IL-6, MCP-1, and TNFα, but showed higher IL-8 level as compared with Group 1. In addition, spontaneous and/or LPS-induced levels of IL-6 and TNFαin Group 2 did not significantly differ from the controls, which presumably also indicated the suppression of their production. In contrast, spontaneous and/or LPS-induced levels of IL-1β, IL-6, MCP-1, and TNFαin Group 1 were higher than in the controls. The spontaneous IL-10 level in the patients from both groups were higher than in the controls. Peripheral blood lymphocyte and T-cytotoxic T-lymphocyte counts in both groups of TBE patients were lower than in the controls. There was significant increase in neutrophil counts, decrease in NK cell count in Group 2 as compared to the patients with a milder febrile form.Conclusion.Meningeal acute TBE patients was presumably associated with inadequate immune response with NK cell deficiency, T-cell dysfunction, increased neutrophil count in the peripheral blood and impaired pro-inflammatory cytokine production related to innate immune response.